Challenges and opportunities of Ageing Population - Leeson, George; Drazic, Leonardo; Klein, Alejandro (REVISTA EUROLATINOAMERICANA DE ANÁLISIS SOCIAL Y POLÍTICO, 2020)
The advanced demographic transition is increasingly categorizing the need to address issues that are establishing patterns of how social events will be built in the next 50, 100 years and beyond. The fact that we are about to achieve, if it has not already been achieved, a radical population recomposition is becoming more and more important: one third of the population will be transformed into elderly people. One out of every three inhabitants will be 60 years old or older.